PENINGKATAN KETAHANAN PANGAN MASYARAKAT ASLI PAPUA MELALUI PELATIHAN BUDIKDAMBER PLUS AKUAPONIK - Riza Fachrizal; Astaman Amir; Nina Maksimiliana Ginting; Nurhaya Panga (Musamus Devotion Journal, 2021)
The Covid-19 pandemic has affected various aspects of people's lives, including increasing food insecurity. Efforts to improve community food security can be carried out not only through the provision of physical food, but also through increasing people's income. One of the community groups that are quite vulnerable to experiencing food insecurity is the community group in RT 05 Kamundu Village, Merauke Regency. Community members in Kamundu Village are very dependent on fishing and collecting plant products. This is partly due to the lack of public knowledge about farming or raising fish, due to limited public access to the internet or books, which are the main sources of information. One simple technology that can be used to improve people's food security is Fish Cultivation in Buckets (Budikdamber) plus Aquaponics. This fish and vegetable polyculture system has the advantage of not requiring additional equipment such as pumps and filters. This system is very simple so that it is easily adopted by the community. In this service program, we train and assist indigenous Papuans in RT 05, Kamundu Village to carry out Budikdamber plus Aquaponics. This service activity includes training on making Budikdamber plus aquaponics and mentoring. This training combines lecture and demonstration methods. The result of this Community Partnership Service program is that the community is able to use and continue the 4 existing Budikdamber plus Aquaponics technology packages and add these technology packages independently. Another outcome is the availability of vegetables and fish produced by Budikdamber plus Aquaponics that can be consumed or sold by the community, thereby increasing food security.